International influences and Baptist mission in West Cameroon : German-American missionary endeavor under international mandate and British colonialism - Weber, Charles William, 1945- (Studies in Christian Mission, 1993)
This study presents a history, based on original archival and primary source material, of the Baptist mission educational situation of Cameroon province from 1922 to 1945. The provisions of the League of Nations' mandate, under which Great Britain administered the province in this period, included 'complete freedom of conscience and the free exercise of all forms of worship', yet from the beginning of the Mandate clear tensions existed. The missions desired education to serve evangelical purposes, while the colonial government strove for a uniform adaptionist program, suited to European perceptions of the abilities, traditions and local conditions of the African peoples. The work relates thus to a number of themes: European colonialism; the Mandate system; international theories of education; a comparison of British, American and German influences; cross-cultural mission work; and the personal contributions of three particular missionaries: Bender, Gebauer and Dunger.